Between ʿAql and Naql: Negotiating Reason and Revelation in the Islamic Intellectual Tradition - Nazir Ahmad Zargar (LECTURES: Journal of Islamic and Education Studies, 2025)
This paper examines the relationship between ʿaql (human reason) and naql (divine revelation) in Islamic intellectual history. After defining these terms, it studies classical perspectives from early rationalists to Abū al-Ḥasan al-Ashʿarī (874–936 CE) and Abū Manṣūr al-Māturīdī (853–944 CE) theologians on whether apparent conflicts between reason and scripture can arise. Drawing on Qur’anic tafsīr and theological works of scholars like al‑Ghazzālī (1058–1111) and Ibn Taymiyyah (1263–1328), the study shows how genuine contradiction is considered impossible (since both reason and revelation originate from One Single God — Allāh ﷻ) but how unusual instances like mu‘jizāt (miracles) and ghāʾib (the unseen) may challenge habitual expectations. Case studies, like the ḥadīth about the fly, the Qur’ān (13:12-13) on lightning and thunder, and Day of Judgment signs like the westward sunrise, illustrate how premodern and contemporary scholars distinguish contrary to reason (logically impossible) from contrary to habit (empirically rare). A comparison between scientific reasoning and daily experiences with scriptural texts is made to show that true reconciliation involves contextual interpretation, recognition of the limits of reason, and assent to divine omnipotence. The paper concludes that in mainstream Sunni thought, reason and revelation are ultimately harmonious: any apparent conflict must be addressed by careful analysis, metaphorical readings, or admission that human knowledge is incomplete.